Flow dynamics studies in the NETmix reactor for a large range of flowrate ratios between feed streams
The mixing dynamics that occur inside the NETmix reactor have been previously thoroughly studied for equal feed streams distributed through the inlets. To broaden the applicability of this static mixer, this work intends to expand the knowledge of the mixing dynamics mechanisms for cases where dissimilar inlet flowrates are imposed. Computational Fluid Dynamics (CFD) tools were used to simulate flow dynamics experiments in a reduced NETmix geometry for different inlet flowrate ratios. The simulation results show that this reactor can attain the desirable condition of similar outlet flowrates for several dissimilar inlet flow conditions. A flow dynamics analysis enabled the determination of the natural frequency of oscillation of the flow and related it to the volume of the chambers occupied by vortices. Finally, the velocity fluctuations at the centre of NETmix chambers were characterised in terms of the intensity of turbulence.